2009
DOI: 10.1124/mol.109.059915
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Activation of Soluble Guanylate Cyclase by the Nitroxyl Donor Angeli's Salt

Abstract: Nitroxyl (HNO) may be formed endogenously by uncoupled nitric-oxide (NO) synthases, enzymatic reduction of NO or as product of vascular nitroglycerin bioactivation. The established HNO donor Angeli's salt (trioxodinitrate, AS) causes cGMPdependent vasodilation through activation of soluble guanylate cyclase (sGC). We investigated the mechanisms underlying this effect using purified sGC and cultured endothelial cells. AS (up to 0.1 mM) had no significant effect on sGC activity in the absence of superoxide dismu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 40 publications
(53 reference statements)
1
49
3
2
Order By: Relevance
“…Furthermore, it has been shown that HNO stimulates sGC to suppress cardiomyocyte hypertrophy (Lin et al, 2012). In contrast, Zeller's group reported an intracellular oxidation of HNO to NO following the activation of sGC (Zeller et al, 2009). Our data do not clarify whether HNO itself directly activated sGC (Fukuto et al, 1992) or went through the intermediary of NO following intracellular oxidation (Zeller et al, 2009).…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, it has been shown that HNO stimulates sGC to suppress cardiomyocyte hypertrophy (Lin et al, 2012). In contrast, Zeller's group reported an intracellular oxidation of HNO to NO following the activation of sGC (Zeller et al, 2009). Our data do not clarify whether HNO itself directly activated sGC (Fukuto et al, 1992) or went through the intermediary of NO following intracellular oxidation (Zeller et al, 2009).…”
Section: Discussioncontrasting
confidence: 53%
“…We utilized carboxy-PTIO in the present study to reveal potential NO˙-mediated actions (10,42,59) in response to both donors. It should be noted, however, that carboxy-PTIO is a mixed NO˙-peroxynitrite scavenger (41,54,62). We thus cannot exclude the possibility that carboxy-PTIO removed both NO˙and peroxynitrite in the presence of ET 1 and DEA-NO; given that both IPA-NO and DEA-NO markedly suppressed ET 1 -stimulated cardiomyocyte superoxide generation, it is, however, unlikely that there is detectable peroxynitrite in our cardiomyocyte preparations.…”
Section: Discussionmentioning
confidence: 76%
“…However, the thiol dithiothreitol (DTT), which blocks nitroxyl (NO À )-mediated cysteine modification (S-nitrosylation) but not NO (NO. )-dependent sGC activation, [34][35][36] did not protect cultured cells from SNAP cytotoxic stimulus (59.5 ± 9.5%, N ¼ 3, one-way analysis of variance (ANOVA)) in E6 purified retinal cultures, which argues against an S-nitrosylation-dependent mechanism for NO to increase death of E6 neurons. To corroborate our pharmacological data further, we used a lentiviralmediated shRNA delivery system to knockdown cGKII specifically in retinal mixed cultures ( Figure 3e) and evaluated SNAP-induced cell death or survival by using ethidium homodimer-1 (EthD1) labeling (Figure 3f) or 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay (Figures 3g and h).…”
Section: Resultsmentioning
confidence: 94%